MESIN PENCACAH PELEPAH SAWIT - Widyarini, Widyarini; Sukadi, Sukadi; Saputra, Yoga (Smart Education, 2025)
Abstract: Palm oil farmers utilize oil palm frond waste, where the fronds can serve as a source of feed for cattle and goats, as well as a medium for compost fertilizer. However, the processing is still done manually and traditionally. Based on this condition, a designer came up with the idea to create a palm frond shredding machine, which consists of cutting blades and shredding blades, aimed at assisting the shredding process. The machine includes several components to support the shredding process, such as a cutting blade disc, a shaft, and a fan plate. It is equipped with a total of 38 blades, comprising 4 cutting blades and 34 shredding blades. The shredding blades are 21.5 cm long, while the cutting blades are 20 cm in length. All blades are made from automotive spring steel, making them strong and suitable for use as cutting tools in a palm frond shredding machine. The output produced by this machine is well-processed and helps farmers in the palm frond shredding process for composting purposes. It also supports environmentally friendly frond processing. Based on testing, the machine operating at 1455 rpm yielded better results in terms of time and shredding quality compared to the 1346 rpm rotation speed.Keyword: Palm fronds, shredding machine, shredding blade, rotation speed.Abstrak: Para petani sawit memanfaatkan limbah pelepah sawit dimana pelepah bisa menjadi sumber pakan ternak sapi maupun kambing dan juga bisa menjadi media untuk dijadikan pupuk kompos. Namun proses pengolahannya masih secara manual dan tradisional. Berdasarkan hal tersebut perancang melakukan ide untuk membuat suatu mesin pencacah pelepah sawit yang mana terdiri dari pisau potong dan pisau pencacah, yang nantinya akan membantu proses pencacahan dari sebuah mesin pencacah pelepah sawit. Mesin tersebut memiliki beberapa komponen dalam membantu proses cacahan diantaranya yaitu piringan pisau potong, poros dan plat kipas. Mesin ini memiliki jumlah pisau sebanyak 38 buah diantaranya terdiri dari 4 pisau potong dan 34 pisau pencacah. Pisau pencacah memiliki panjang 21,5 cm kemudian untuk pisau potongnya memiliki panjang 20 cm, dan pisau itu sendiri terbuat dari bahan pegas mobil yang tentunya kuat untuk digunakan sebagai mata pisau dari mesin pencacah pelepah sawit. Dan hasil yang didapatkan mesin pencacah tersebut terolah secara sempurna, dan membantu petani untuk melakukan proses pencacahan pelepah sawit guna pupuk kompos, serta membantu para petani dalam mencacah pelepah sawit yang ramah lingkungan. Hasil pengujian dari data yang diperoleh pada putaran 1455 rpm memiliki hasil yang lebih baik dalam hal waktu dan cacahan dibanding dengan putaran pada 1346 rpm.Kata kunci : Pelepah sawit, mesin pencacah, pisau pencacah, putaran